2022
DOI: 10.3390/pathogens11040434
|View full text |Cite
|
Sign up to set email alerts
|

Paramyxovirus Diversity within One Population of Miniopterus fuliginosus Bats in Sri Lanka

Abstract: Bats are known as typical reservoirs for a number of viruses, including viruses of the family Paramyxoviridae. Representatives of the subfamily Orthoparamyxovirinae are distributed worldwide and can cause mild to fatal diseases when infecting humans. The research on Paramyxoviruses (PMVs) from different bat hosts all over the world aims to understand the diversity, evolution and distribution of these viruses and to assess their zoonotic potential. A high number of yet unclassified PMVs from bats are recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Furthermore, the global interest of bats as potential reservoir hosts of zoonotic pathogens was highlighted recently as these flying mammals have been detected to be harboring coronaviruses [22]. In addition, recent studies revealed the presence of alpha-and betacoronaviruses in Miniopterus fuliginosus and Rousettus leschenaultii bats and paramyxoviruses in Miniopterus fuliginosus inhabiting the Wavulgalge cave, Sri Lanka [23][24][25]. Therefore, adequate PPE was worn during animal capturing, handling, and sample collection to reduce the potential risk of exposure to zoonotic or anthropozoonotic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the global interest of bats as potential reservoir hosts of zoonotic pathogens was highlighted recently as these flying mammals have been detected to be harboring coronaviruses [22]. In addition, recent studies revealed the presence of alpha-and betacoronaviruses in Miniopterus fuliginosus and Rousettus leschenaultii bats and paramyxoviruses in Miniopterus fuliginosus inhabiting the Wavulgalge cave, Sri Lanka [23][24][25]. Therefore, adequate PPE was worn during animal capturing, handling, and sample collection to reduce the potential risk of exposure to zoonotic or anthropozoonotic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid was added later during the preparation process of the samples in the laboratory. In terms of molecular biological analyses, this method did not impair the outcome of the analyses as we were able to detect different viruses via PCR and in NGS analyses [11, 12, 18]. The presence of intact virus particles has not been tested yet, and virus isolation in cell culture will be performed in future analyses.…”
Section: Discussionmentioning
confidence: 99%
“…They contribute to the agro-ecosystems by pollination, seed dispersal and insect control, which renders them particularly interesting for ecological research and conservation biology [9,10]. Although the general ecology of bats in Sri Lanka is well studied, so far only few scientific studies on their role as viral reservoirs have been published [9,[11][12][13][14]. With this case study, we present the establishment of an interdisciplinary field study on bat species inhabiting Wavul Galge cave (Koslanda, Sri Lanka).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, only few studies have focused on bats as reservoir host for pathogens in Sri Lanka [1518]. Here we present the first virome analysis of M. fuliginosus bats inhabiting Wavul Galge cave (Koslanda, Sri Lanka) in the interior of Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…In three individual field studies at different time points, we captured bats of all representative species and collected different sample material depending on availability [19]. Selected sample sets had been analyzed in previous investigations focusing on different research questions [17, 18, 20, 21]. In this study, we focus on the virome analysis of urine swabs (US), oral swabs (OS) and feces (F) collected from M. fuliginosus bats at one sampling point (July 2018).…”
Section: Introductionmentioning
confidence: 99%